2015
DOI: 10.1103/physreve.91.052128
|View full text |Cite
|
Sign up to set email alerts
|

Hidden entropy production by fast variables

Abstract: We investigate nonequilibrium underdamped Langevin dynamics of Brownian particles that interact through a harmonic potential with coupling constant K and are in thermal contact with two heat baths at different temperatures. The system is characterized by a net heat flow and an entropy production in the steady state. We compare the entropy production of the harmonic system with that of Brownian particles linked with a rigid rod. The harmonic system may be expected to reduce to the rigid rod system in the infini… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
33
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 36 publications
1
33
1
Order By: Relevance
“…Many systems made of two or more interacting Brownian particles have been considered where each reservoir acts on a different particle (see, e.g., Refs. [5,37,40,41]). Various models of Feynman ratchets [42] fall for instance into this category [4,38,43,44].…”
Section: Introductionmentioning
confidence: 99%
“…Many systems made of two or more interacting Brownian particles have been considered where each reservoir acts on a different particle (see, e.g., Refs. [5,37,40,41]). Various models of Feynman ratchets [42] fall for instance into this category [4,38,43,44].…”
Section: Introductionmentioning
confidence: 99%
“…Some time ago we suggested that the Schnakenberg entropy production is not an equality but only a lower bound for the actual entropy production in the environment [25]. This claim was first proven by Esposito [26] in a thermodynamic setting and then developed further in the context of hidden entropy production [27,28]. In this approach the subsystems are always in contact with heat baths which allows one to quantify the corresponding energy, work, heat transfer, and entropy flow.…”
Section: Introductionmentioning
confidence: 99%
“…(1). On the other hand, the FT is not expected to hold, if the total entropy production is measured by considering only system A [32][33][34][35][36][37][38][39][40]. Therefore, any deviations from the FT as given by eq.…”
mentioning
confidence: 99%